2021
DOI: 10.2147/dmso.s317371
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Weight, Dysglycemia, and Dyslipidemia After Moderately Low-Carbohydrate Diet Education (LOCABO Challenge Program) Among Workers in Japan

Abstract: Purpose It is theorized that the prevalence of obesity has not decreased owing to poor adherence to implemented programs addressing metabolic syndrome, obesity, and diabetes in Japan. Therefore, we intended to evaluate the influence of a moderately low-carbohydrate diet on improving markers of metabolic syndrome among workers in Japan. Patients and Methods Participants with metabolic syndrome or obesity were recruited based on the eligibility criteria for the Specific H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Other studies have found that low carbohydrate intakes have a protective effect against obesity, but most of them examined obese people who restricted their carbohydrate intakes [ 32 , 33 , 34 , 35 ]. Proponents of an LC diet argue that it can increase energy expenditure by 400 to 600 kcal/d, equivalent to an hour of moderate PA.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that low carbohydrate intakes have a protective effect against obesity, but most of them examined obese people who restricted their carbohydrate intakes [ 32 , 33 , 34 , 35 ]. Proponents of an LC diet argue that it can increase energy expenditure by 400 to 600 kcal/d, equivalent to an hour of moderate PA.…”
Section: Discussionmentioning
confidence: 99%
“…In the diet, several factors influence hyperlipidemia, including the amount of carbohydrates, the type of sugar (glucose, fructose, sucrose, lactose), the nature of starch and the size of the carbohydrate particle (RICCARDI; RIVELLESE, 2000). A calorie-restricted diet in the treatment of obesity significantly reduces the serum triglycerides levels, as dietary carbohydrate intake and obesity are associated with high levels of triglycerides (YAMADA et al, 2021). The use of low-calorie diets with high protein and fiber levels and low carbohydrate and lipid levels reduces glycemia, cholesterol and triglyceride levels (CLINE et al, 2021), which proves that diets with low lipid values allow the reduction of hyperlipidemia and decrease in these values even in those animals that show cholesterol, triglycerides, glycemia and blood pressure parameters within the normal range (PEREIRA NETO et al, 2010;VERKEST, 2014;PÉREZ-SÁNCHES et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in laboratory values from baseline to the last medical checkup (days 366–730 from the index date) were calculated by stratification according to the presence or absence of new prescriptions. In these patients, the number and percentage of patients exceeding the standard reference range or treatment‐recommended criteria 14 , 15 , 16 , 17 in the laboratory values were summarized at the baseline and the last medical checkup: in population I, systolic blood pressure (SBP) ≥130 mmHg or diastolic blood pressure (DBP) ≥85 mmHg (exceeding the standard reference range), or SBP ≥140 mmHg or DBP ≥90 mmHg (exceeding the treatment‐recommended criteria); in population II, uric acid ≥7.0 mg/dL (exceeding the treatment‐recommended criteria); and in population III, TG ≥150 mg/dL or low‐density lipoprotein (LDL) cholesterol ≥120 mg/dL (exceeding the standard reference range). If patients had two or more medical checkup data, the laboratory data closest to day 730 were adopted.…”
Section: Materials and Methodsmentioning
confidence: 99%